Effect of CNG in a fuel dose on the combustion process of a compression-ignition engine - Mikulski, Maciej; Wierzbicki, Sławomir; Śmieja, Michał; Matijošius, Jonas (Transport, 2015)
Currently, one of the major trends in the research of contemporary combustion engines involves the potential use of alternative fuels. Considerable attention has been devoted to methane, which is the main component of Natural Gas (NG) and can also be obtained by purification of biogas. In compression-ignition engines fired with methane or Compressed Natural Gas (CNG), it is necessary to apply a dual-fuel feeding system. This paper presents the effect of the proportion of CNG in a fuel dose on the process of combustion. The recorded time series of pressure in a combustion chamber was used to determine the repeatability of the combustion process and the change of fuel compression-ignition delay in the combustion chamber. It has been showed that NG does not burn completely in a dual-fuel engine. The best conditions for combustion are ensured with higher concentrations of gaseous fuel. NG ignition does not take place simultaneously with diesel oil ignition. Moreover, if a divided dose of diesel is injected, NG ignition probably takes place at two points, as diesel oil.